A sensitive UPLC-MS/MS method for simultaneous quantification of one-carbon metabolites & co-factors in human plasma - Chen, Ping; Tang, Yun; He, Qiangqiang; Liu, Lishun; Zhou, Ziyi; Song, Yun; Zhang, Nan; Wang, Binyan; Zhou, Houqing; Shi, Hanping; Jiang, Jie (Journal of pharmaceutical and biomedical analysis, 2022)
One-carbon metabolism is an important metabolic pathway involved in many diseases, such as congenital malformations, tumours, cardiovascular diseases, anaemia, depression, cognitive diseases and liver disease. However, the current methods have specific defects in detecting and qualifying the related compounds of one-carbon metabolism. In this study, a validated method was established to simultaneously quantify 22 one-carbon metabolites & co-factors in human plasma and applied to the study of correlation between one-carbon metabolism and colorectal cancer in human plasma samples, which were from 44 healthy subjects and 55 colorectal cancer patients. The method used ultra-high performance liquid chromatography coupled with triple quadrupole mass spectrometry (UPLC-MS/MS), and the analytes included betaine, L-carnitine, L-cystathionine, L-cysteine, dimethylglycine, DL-homocysteic acid, homocysteine, methionine, pyridoxal hydrochloride, pyridoxamine dihydrochloride, pyridoxine dihydrochloride, S-(5′-Adenosyl)-L-homocysteine, serine, choline chloride, folic acid, glycine, pyridoxal phosphate monohydrate, riboflavin, taurine, 5-methyltetrahydrofolate, S-(5′-adenosyl)-L-methionine disulfate salt, trimethylamine oxide. The developed method was successfully applied to the quantification of 22 one-carbon metabolites & co-factors in human plasma from colorectal cancer patients and healthy individuals. The plasma concentrations of dimethylglycine was significantly decreased in the patients compared with the healthy individuals, while L-cystathionine was increased. •One-carbon metabolism is involved in many diseases.•A UPLC-MS/MS method was developed to quantify one-carbon metabolites & co-factors.•This method was suitable for extensive clinical application.•Correlation between one-carbon metabolism and colorectal cancer was observed.